Understanding the Chinese economies - Guo, Rongxing (Academic Press, 2012)
China's economic growth has been more robust in some regions than others. In a country as large as China, examinations of regional differences can provide a viable way to learn about the economy as a whole. Rongxing Guo provides a systematic introduction to the economies of China by describing their external and internal drivers and by placing them within geopolitical and even socio-cultural boundaries. His pairings of case studies and empirical techniques reveal a rich, deep appreciation of the growth process and of interactions between key factors. This book delves more deeply into issues surrounding the economy than other books, offering a unique and important perspective that many will find useful. Covering history and administrative structures, unique economic features, some domestic economic issues, and international economic engagement, it describes an often inaccessible perspective with nuances all students of China will find valuable. Introduces China's regional economies, often overlooked in US and European texts within larger contexts of social and geopolitical concerns Explains the reform process since 1978 in a comprehensive, non-technical, and accessible mannerIncludes online ancillaries of documents, links, and more, expanding the text and keeping it up-to-date. Features case studies in each chapter.